Antiplatelets in patients with atrial fibrillation: a systematic review and meta-analysis of randomized clinical trials. (24th May 2021) - Benz, A; Johansson, I; Dewilde, W; Lopes, RD; Mehran, R; Sartori, S; Sarafoff, N; Yasuda, S; Mcintyre, WF; Healey, JS; Shoamanesh, A; Eikelboom, JW; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Dr. Benz reports a personal research grant from the German Heart Foundation (Deutsche Herzstiftung e.V.). Dr. Johansson reports personal unrestricted research grants from Swedish Heart-Lung Foundation (Hjärt-Lungfonden) and from Stockholm County Council (Region Stockholm). Dr. McIntyre holds a fellowship award from the Canadian Institutes for Health Research (CIHR). Dr. Shoamanesh reports funding support from the Marta and Owen Boris Foundation and the Heart and Stroke Foundation of Canada. Background/Introduction: There is an ongoing controversy surrounding the efficacy and safety of antiplatelet agents in patients with atrial fibrillation (AF). Purpose: We aimed to systematically assess the effects of antiplatelets on stroke and other outcomes in patients with AF, both receiving oral anticoagulation or not. Methods: We searched MEDLINE, Embase and CENTRAL up until September 2020 to identify randomized trials allocating patients with AF to aspirin or a P2Y12 inhibitor, versus control. Where applicable, we obtained unpublished data from study authors. Random-effects models were applied for meta-analysis. Results: Based on 21, 518 patients from 18 randomized trials, there was no reduction in stroke with antiplatelet therapy (risk ratio [RR] 0.89, 95% confidence interval [CI] 0.76-1.04). There was a significant qualitative interaction according to whether patients were receiving concomitant oral anticoagulation or not (p < 0.001). Without concomitant anticoagulation, antiplatelets reduced stroke (RR 0.77, 95% CI 0.69-0.86), while they appeared to increase stroke with it (RR 1.33, 95% CI 0.98-1.79). A similar pattern emerged for ischaemic stroke. Antiplatelets increased major bleeding (RR 1.54, 95% CI 1.35-1.77) and intracranial haemorrhage (RR 1.64, 95% CI 1.20-2.24), and reduced myocardial infarction (RR 0.79, 95% CI 0.65-0.94), consistently and irrespective of concomitant anticoagulation. Antiplatelets had a neutral effect on mortality (RR 1.02, 95% CI 0.89-1.17). Conclusions: Antiplatelet therapy did not reduce stroke and increased major bleeding in patients with AF. Antiplatelets did not affect mortality. Subgroup analysis suggests a reduction in stroke with antiplatelets in patients without concomitant oral anticoagulation, and a corresponding signal for harm in those with it.